A yeast-based assay system for the study of environmentally induced copy number variation - Stanton, Jacquelyn Lee, author; Argueso, Juan Lucas, advisor; Legare, Marie, committee member; Stargell, Laurie, committee member (Colorado State University. Libraries, 2012)
Multiple studies have shown that in different individuals, specific genomic segments can occur at a variable copy number relative to the reference human genome. Chromosomal rearrangements resulting in Copy Number Variations (CNVs) have long been recognized as contributing factors in carcinogenesis, and more recently in Autism Spectrum Disorders. The molecular mechanisms underlying the formation of CNVs are not completely understood. The goal of this research project was to complete the development of an assay system to study CNV, and to validate it as a tool to investigate the relationship between environmental exposures and CNV formation. We have optimized a CNV detection assay using the budding yeast Saccharomyces cerevisiae as an experimental model system. This CNV reporter contains two yeast genes, SFA1 and CUP1 that confer gene dosage-dependent tolerance to formaldehyde and copper, respectively. This system enables the detection of rare clones containing an amplification of the chromosomal segment containing the reporter by selection in media containing high levels of formaldehyde and copper, allowing the estimation of the rate of CNV formation. Results obtained in diploid cells under basal growth conditions (un-induced / un-exposed) showed that most spontaneous CNV events detected in our system were mediated through non-allelic homologous recombination (NAHR) between dispersed repetitive DNA sequences, mainly Ty1 and Ty2 retrotransposable elements and their LTRs. Another set of repeats involved in NAHR included conserved gene family. Single copy sequences and microhomology motifs were detected in our dataset, but were exceedingly rare. The most abundant classes of CNVs observed involved segmental duplications and non-reciprocal translocations. In order to characterize the effect of environmental factors on CNV, cells were exposed to relatively low doses of three different known mutagens: Hydroxyurea, Methyl Methanesulfonate, and Camptothecin. These exposures resulted in an increase of the CNV rate ranging from 3 to 17 fold over the un-induced cultures. The spectra of chromosomal rearrangements induced by these exposures was analyzed, revealing that not only did exposures result in more chromosomal breaks but often a higher frequency of resulting segmental copies, and allowing further understanding of the CNV mechanisms associated with these exposures.